Vegetative development of turiaçu pineapple under two ecological conditions in maranhão, brazil - Ramos, Letícia Moura; Reis, Fabrício de Oliveira; Araujo, José Ribamar Gusmão; Reis, Isaias Dos Santos [UNESP]; Gonçalves, Rawlisson Silva; Neves Junior, Augusto César Vieira (FapUNIFESP (SciELO), 2020)
Pineapple plants of the cultivar Turiaçu are important for the fruit production sector in the state of Maranhão (MA), Brazil, because of their fruit quality and local social and economic value. The objective of the present work was to evaluate characteristics of pineapple plants of the cultivar Turiaçu at vegetative and propagative stages in two places, using two fertilization sources. The study was conducted in the municipalities of Turiaçu and São Luís, MA, using mineral and organic fertilizations. The plants were evaluated for number of leaves and leaf dry weight; stem diameter, length, and dry weight; width, length, and fresh and dry weights of the D leaf; and number of suckers (plantlets). Plants grown in Turiaçu under mineral fertilization had higher number of leaves (up to 162.5% higher) and higher number of suckers (up to 233.3% higher) than those grown in São Luís under organic fertilization. The results of the study indicate that the more favorable climate conditions in the municipality of Turiaçu were decisive for the success of the cultivar, and the organic fertilizer used was not adequate.
Desenvolvimento vegetativo do abacaxi turiaçu sob duas condições ecológicas no maranhão, brasil
Keywords: Ananas comosus var. comosus (L.) Merril; Ecophysiology; Propagation